Colombian Industry 1975-2014: Inequity between Labor and Capital (2017)
As part of a research about transnationalization of the large Colombian capital, functional distribution of the wealth created in the industry for nearly 40 years is analyzed. The changes in the composition of its gross output and the concentration of production and centralization of capital, phenomena led by financial groups dating from the last century, are stand out. It also explores the evolution of labor productivity and employment, and the possible effects of technological change in this sector. It is concluded that in the industrial value added distribution, capital gains weight relative to the detriment of the share of the work.